The Coding Effect of Institutional Ownership on Political and Tax Avoidance Behavior - Muhaimin, Muhaimin; Arman, Andi; Wahid, Abdul; Putriani, Ade Irma; Yunus, Muh (Penerbit Goodwood, 2025)
Purpose: This study investigates the influence of political connections on tax avoidance and examines the moderating role of institutional ownership in Indonesia’s mining sector. Methodology: Quantitative research with a causal approach was conducted using a sample of 18 mining companies listed on the Indonesian Stock Exchange over four years, totalling 72 observations. Data were analysed using SPSS 24.0, applying Moderated Regression Analysis (MRA). Results: Political connections positively and significantly influenced tax avoidance. However, institutional ownership does not significantly affect tax avoidance and does not moderate the relationship between political connections and tax avoidance. Conclusions: Political connections significantly increase tax avoidance, giving firms favourable treatment. Institutional ownership had no moderating effect. Although legal, tax avoidance harms state revenue, highlighting the need for stricter regulations and transparency. Limitations: This study is limited to mining sector companies in Indonesia, which restricts the generalizability of the findings to other sectors or countries. Further research could compare results across countries with similar economic and cultural contexts, such as developing Asian countries, to enhance their representativeness. Contributions: This study adds to the literature by highlighting the unique role of political connections in tax avoidance within Indonesia's mining sector and demonstrating that institutional ownership may not always serve as an effective moderating factor. It also emphasizes the need for improved regulatory oversight and governance to mitigate tax avoidance practices linked to political affiliations.